THE USE OF TREASURE HUNT GAME IN TEACHING PREPOSITION OF PLACE IN DESCRIBING THINGS - Isnaini, Isnaini; Appriliaswati, Rahayu; Husin, Syarif (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This study aimed to prove whether Treasure hunt game is effective for teaching preposition to the seventh grade students of SMPN 6 in The Academic Year of 2014/2015. The design of this study was pre-experimental design with one group pretest-posttest design. The population of this study was 234 students. The sample was chosen by using cluster random sampling technique. Moreover, the technique to collect the data was measurement technique. Then, the tool of collecting data was written test. It was found that Treasure hunt Game is effective in teaching preposition to the Seventh grade students of SMPN 6. The effectiveness of using Treasure hunt game can be seen based on the researcher finding that the value of t-test was 9.83 which meant bigger than the number of t-table 2.037 in the area of paired sample in 5% of 33 degree of freedom. The researcher concluded that the use of treasure hunt gamewas effective for teaching preposition of place in describing things to the students of SMPN 6 in The Academic Year of 2014/2015. The researcher suggests that the teacher could include treasure hunt game in teaching process as a reference of method that may be used to teach preposition. Keywords:  Effectiveness,Preposition, Treasure Hunt Game